2006
DOI: 10.1159/000095637
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of Histamine Uptake into the Synaptosomes of Rat Brain

Abstract: Histamine has many physiological roles in the brain and periphery. Neuronal histamine is metabolized almost exclusively by histamine N-methyltransferase. Although several neurotransmitter systems such as dopamine and 5-hydroxytryptamine have their specific reuptake system in their neurons and glial cells, a specific histamine reuptake system into the corresponding nerve terminals or glial cells has not yet been clearly elucidated. We characterized the uptake of histamine into the P2 fractions of rat brain homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 80 publications
2
9
0
Order By: Relevance
“…The rate of rat synaptosomal histamine uptake is in the range of fmol/mg of protein/min [23]. These findings also support the idea proposed back in 1987 [37], that astrocytes represent the main inactivation site of histamine in the rat central nervous system when it was documented that histamine had been more readily transported into the astrocyte enriched fraction than into the synaptosomal fraction while the opposite was observed when uptake of histidine was studied.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The rate of rat synaptosomal histamine uptake is in the range of fmol/mg of protein/min [23]. These findings also support the idea proposed back in 1987 [37], that astrocytes represent the main inactivation site of histamine in the rat central nervous system when it was documented that histamine had been more readily transported into the astrocyte enriched fraction than into the synaptosomal fraction while the opposite was observed when uptake of histidine was studied.…”
Section: Discussionsupporting
confidence: 86%
“…The measured K m value was significantly higher than K m obtained by Huszti et al [11] -0.19 µM in astrocytes and 0.30 µM in rat cerebral endothelial cells [33], but similar to the K m value of histamine uptake occurring in the P2 fraction of rat synaptosomes Clearance of histamine into rat type1 astrocytes 99 -1.2 µM [23]. Cultured rat astrocytes express also OCT1, OCT2 and OCT3 [18], of which OCT2 and OCT 3 can also transport histamine, but the K m values for histamine transport by OCTs are significantly different (180-940 µM) [24] than the affinity for histamine uptake obtained in our study, so the observed carrier seems to represent a new entity.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations